Hematopoietic Stem Cell Transplantation for Hepatitis-associated Aplastic Anemia Following Liver Transplantation for Nonviral Hepatitis: A Retrospective Analysis and a Review of the Literature by the Severe Aplastic Anemia Working Party of the European Society for Blood and Marrow Transplantation. Issue 7 (October 2021) - Mohseny, Alexander B.; Eikema, Dirk-Jan A.; Neven, Benedicte; Kröger, Nicolaus; Shaw, Peter J.; Damaj, Ghandi; Dalle, Jean-Hugues; Bosman, Paul V.; Delehaye, Fanny; Lankester, Arjan C.; Smiers, Frans J.; Peffault de Latour, Regis
Abstract : Hepatitis-associated aplastic anemia (HAAA) has been reported in 23% to 33% of patients who received orthotopic liver transplantation (LT) for acute liver disease of unknown origin (nonviral hepatitis). In this situation, hematopoietic stem cell transplantation (HSCT) might be a curative option. Here the authors report on 6 patients who received HSCT after LT for nonviral HAAA hepatitis. The outcomes were interpreted in the context of recently reported immune suppressive therapy (IST) outcomes in 8 patients with HAAA and to HSCT outcomes in patients with HAAA who recovered from hepatitis without undergoing LT. All patients transplanted by using HLA-identical sibling donors (3 of 6) were alive and had normal liver function and hematopoiesis without graft versus host disease. Both patients receiving bone marrow from a matched unrelated donor (MUD) experienced extensive graft versus host disease that was fatal for one patient. Thereby, the authors conclude that HSCT can be considered as a first-choice treatment for this category of patients when HLA-identical donors are available. When no HLA-identical donor is available, IST should be applied as HSCT with other donor sources might be reserved for IST nonresponders or poor responders.